Lee Hayman's Steinbeck room - Art Ring:::Creator::::::::::::
Lee Richard Hayman's Steinbeck room. Mr Hayman was a devoted collector who, in 2004, donated 125 boxes of these materials to the Martha Heasley Cox Center for Steinbeck Studies. Original in safe.